Perbedaan Kebersihan Gigi dan Mulut pada Anak yang Menyikat Gigi dengan Teknik Fone’s dan Teknik Horizontal pada Murid Umur 11-12 Tahun - Risa Erpa Yanti; Syukra Alhamda; Nova Herawati (CV. CENDIKIA JENIUS INDONESIA, 2023)
Dental and oral health problems that occur are generally caused by dental plaque which is the main agent causing dental and oral diseases such as dental caries and periodontal tissue diseases. Plaque control can be done mechanically by brushing your teeth. The purpose of this study was to see whether or not there were differences in brushing teeth with the fone’s technique and horizontal technique on dental and oral hygiene in students aged 11-12 years at SDN 04 and SDN 01 Batipuah Baruah, Batipuh District, Tanah Datar District. This study used a quasi-experimental method with a pretest and post-test design. Sampling using saturated sampling technique with inclusion criteria as many as 62 people. Data collection through observastion treatment. The results of data analysis using statistical tests with the T-test showed that there was no significant difference between oral hygiene (HI) in students aged 11-12 years who brushed with the fone’s technique and the horizontal technique with ɑ (0,126 > 0,05), but on average there is a difference of 42,48% : 33,35%. The fone’s technique and the horizontal technique can both increase the dental and oral hygiene score. It is recommended for students of SDN 04 and SDN 01 Batipuah Baruah to brush their teeth with the fone’s technique and the horizontal technique routinely at least 2x a day to prevent dental and oral diseases.